A No-Code Approach for Intuitive Robot Programming for Agile Welding Application - Halim, Jayanto; Bdiwi, Mohamad; Ihlenfeldt, Steffen (2024 IEEE International Symposium on Robotic and Sensors Environments (ROSE), 2024)
Agile manufacturing paradigms have revolutionized a new era of production processes, offering unparalleled flexibility and adaptability to the ever-changing landscape of product variations and smaller batch sizes. In response to this dynamic environment, the robotic industry has undergone a significant transformation, presenting a range of versatile robotic systems capable of swiftly deploying diverse applications. This transformative shift accelerates manufacturing processes and showcases the ability to accommodate product specifications and batch size variations. Welding is a notable example of robotics playing a crucial role in agile production. This work presents a novel approach combining no-code robot programming and an intelligent vision-based welding system. By leveraging this framework, even non-expert users can seamlessly instruct welding trajectories through intuitive interactions. These trajectories are meticulously crafted using advanced welding seam extraction algorithms, considering various welding joint types and inputs from heterogeneous sensors. Consequently, robot-specific parameters can be parametrized, and the generated robot code can seamlessly translate into robotic movements in the real world. Validation of this approach through real-world experiments underscores its potential for deployment in agile welding applications. The promising results affirm this novel methodology's efficacy, paving the way for its practical implementation in real-world scenarios. By effectively bridging the divide between advanced robotics and agile manufacturing, this approach can potentially elevate industrial robotic applications to new levels of efficiency and adaptability.